ЕМОЦІЙНИЙ ФАКТОР НАВЧАННЯ УЧНІВ: ЗМІСТ, СТРУКТУРА ТА ЗНАЧЕННЯ У ЗАБЕЗПЕЧЕННІ ЯКОСТІ ОСВІТИ (Педагогіка вищої та середньої школи, 2009)
The article deals with the problem of the emotional factor of instruction structure and essence. Author defines the notion emotional factor of instruction establishes the significance of emotional factors at the guaranteeing quality of the modern education.